Coronavirus Interplay With Lipid Rafts and Autophagy Unveils Promising Therapeutic Targets - Fecchi, Katia; Anticoli, Simona; Peruzzu, Daniela; Iessi, Elisabetta; Gagliardi, Maria Cristina; Matarrese, Paola; Ruggieri, Anna (Frontiers in Microbiology, 2020)
Coronaviruses are enveloped, single-stranded, positive-sense RNA viruses that can infect animal and human hosts. The infection induces mild or sometimes severe acute respiratory diseases. Nowadays, the appearance of a new, highly pathogenic and lethal coronavirus variant, SARS-CoV-2, responsible for a pandemic (COVID-19), represents a global problem for human health. Unfortunately, only limited approaches are available to treat coronavirus infections and a vaccine against this new coronavirus variant is not yet available. The plasma membrane microdomain lipid rafts have been found by researchers to be involved in the replication cycle of numerous viruses, including coronaviruses. Indeed, some pathogen recognition receptors for coronaviruses as for other viruses cluster into lipid rafts, and it is therefore conceivable that the first contact between virus and host cells occurs into these specialized regions, representing a port of cell entry for viruses. Recent data highlighted the peculiar pro-viral or anti-viral role played by autophagy in the host immune responses to viral infections. Coronaviruses, like other viruses, were reported to be able to exploit the autophagic machinery to increase their replication or to inhibit the degradation of viral products. Agents known to disrupt lipid rafts, such as metil-β-cyclodextrins or statins, as well as autophagy inhibitor agents, were shown to have an anti-viral role. In this review, we briefly describe the involvement of lipid rafts and autophagy in coronavirus infection and replication. We also hint how lipid rafts and autophagy may represent a potential therapeutic target to be investigated for the treatment of coronavirus infections.